EXPERIENCE OF SEVERE SYSTEM TYPE OF JUVENILE RHEUMATOID ARTHRITIS TREATMENT WITH CYCLOSPORINE IN COMBINATION WITH DIFFERENT METHOTREXATE REGIMEN - T.M. Bzarova; E.I. Alexeeva; S.I. Valieva; A.O. Lisitsin ("Paediatrician" Publishers LLC, 2009)
The article presents the case report of early debut and severe course of system type of juvenile rheumatoid arthritis, refractory to methotrexate and blockers of tumor necrotizing factor _ monotherapy. Successful treatment with cyclosporine in daily dose 4.4 mg/kg of body weight combined with different regimen of methotrexate was described. Combined treatment with cyclosporine in daily dose 4.4 mg/kg of body weight and methotrexate in dose 15 mg/m2 of body surface once weekly intramuscularly and 50 mg/m2 of body surface once weekly intravenously during 8 weeks with further dose decrease to 25 mg/m2 of body surface intramuscularly induced remission development in 2-6 months, provided restoration of joints function, increased quality of life. Cyclosporine combined with pulse-therapy with methotrexate in more early stages stopped extra articulate signs of disease and reduced acute inflammatory joint's lesions.Key words: children, juvenile rheumatoid arthritis, cyclosporine, methotrexate.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):142-150)